Validity of Vocational Pedagogy Constructs Using the Rasch Measurement Model - Md Yunus, Jailani; Alias, Maizam; Ibrahim Mukhtar, Marina; Foong, Lee Ming; Kiong, Tee Tze; Rubani, Siti Nur Kamariah; Yunus, Faizal Amin Nur; Hamid, Hashima; Sulaiman, Junita; Sumarwati, & Sri (Journal of Technical Education and Training, 2017)
This study was conducted to generate empirical evidence on the validity and reliability of the items of a new vocational pedagogy instrument. Two stage processes were used to identify and validate constructs. The first stage involves the identification of constructs using exploratory factor analysis method and the second stage was construct validation stage using the Rasch measurement model. Construct validity was examined by analyzing the point-measure correlation index (PTMEA), infit and outfit MNSQ values; while the reliability was examined by analyzing item reliability index. The instrument was distributed to 183 teachers from Malaysian and Indonesian vocational institutions. EFA indicate the presence of construct from 2 sections (Learning Content and Pedagogical Decision). Further analysis using the Rasch measurement model indicates that the reliabilities were between 0.77 to 0.91 and 0.97 to 10.13 for the Learning Content and Pedagogy Decision constructs respectively. PTMEA values are positive for Learning Content constructs indicating that all items are able to distinguish between abilities of respondents but 3 items from Pedagogical Constructs shows there were not moving in line with other items to measure the constructs. However that item was retained with refinement. In conclusion, this study has established valid constructs for development of instrument for assessing vocational pedagogy.